Water compatibility of M’sila region (South- East Algeria) for cultivation of Spirulina & evaluation of methods of extraction of Phycocyanin and investigation of stability by β-Cyclodextrin - Zidane, Salima; Bouleghlem, Hocine; Mohamed Seghir, Abdallah (Emirates Journal of Food and Agriculture, 2022)
Spirulina (Arthrospira platensis) is a microalga that has existed for more than three billion years. It belongs to the family of cyanobacteria. It is extraordinary, rich in nutrients such as proteins, carbohydrates, lipids, vitamins, and minerals. In addition, Spirulina is rich in phycocyanin, a blue protein pigment. It can be used as a dye in food, pharmacology, and cosmetics. Our work focused first on the compatibility of the waters of M’sila region (southeast Algeria) for the cultivation of Arthrospira platensis. Then, we evaluated several methods of extracting phycocyanin to be able to determine the optimal method in terms of yield. We have succeeded in developing a new extraction method coupled with maceration in a glycerol-water mixture with a molar ratio (8/2) assisted by ultrasound with a yield of 52.93 mg/g. The excellent results obtained may be due to the salinity of the waters of the region, to the used nutrient culture medium and/or the climate change of the region. We have formed an inclusion complex between phycocyanin and β-Cyclodextrin to keep it and make it more stable. The encouraging results allow Algeria to gain a foothold on the world market as a producer of blue goldSpirulina (Arthrospira platensis) is a microalga that has existed for more than three billion years. It belongs to the family of cyanobacteria. It is extraordinary, rich in nutrients such as proteins, carbohydrates, lipids, vitamins, and minerals. In addition, Spirulina is rich in phycocyanin, a blue protein pigment. It can be used as a dye in food, pharmacology, and cosmetics. Our work focused first on the compatibility of the waters of M’sila region (southeast Algeria) for the cultivation of Arthrospira platensis. Then, we evaluated several methods of extracting phycocyanin to be able to determine the optimal method in terms of yield. We have succeeded in developing a new extraction method coupled with maceration in a glycerol-water mixture with a molar ratio (8/2) assisted by ultrasound with a yield of 52.93 mg/g. The excellent results obtained may be due to the salinity of the waters of the region, to the used nutrient culture medium and/or the climate change of the region. We have formed an inclusion complex between phycocyanin and β-Cyclodextrin to keep it and make it more stable. The encouraging results allow Algeria to gain a foothold on the world market as a producer of blue gold